1996
DOI: 10.1007/bf00212678
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity of several organophosphorous insecticides and protection by cholinergic antagonists and 2-PAM on Artemia salina larvae

Abstract: The acute toxicity of chlorpyrifos, methylchlorpyrifos, parathion and methylparathion to three age classes of Artemia salina was determined. In general, A. salina 24-h old was less sensitive to these organophosphorous insecticides (OPI) than A. salina 48-h old and A. salina 48-h old was significantly more tolerant than A. salina 72-h old, in contrast, chlorpyrifos was equally toxic to A. salina 48- and 72-h old. There were some differences among the three age classes of A. salina in the relative order of toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 31 publications
3
11
0
1
Order By: Relevance
“…Even still, one of 18 methanolic extracts, LEGE 06071, induced acute effects on the A. salina nauplii with a LC 50 of 17.81 mg mL -1 (95% confidence interval of 11.63 to 27.30 mg mL -1 ). It was also observed that the LC 50 values calculated were more prominent at 48 h, which confirms the sensitivity of nauplii observed in previous works [3,8], suggesting that toxicity is much higher after 48 h exposure than after 24 h. Moreover, previous work showed that the crude extracts of marine Synechocystis strains reduced the survival of A. salina nauplii similarly to the results obtained here [11]. The most toxic extracts in this work were those of the filamentous forms Leptolyngbya and Microcoleus.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Even still, one of 18 methanolic extracts, LEGE 06071, induced acute effects on the A. salina nauplii with a LC 50 of 17.81 mg mL -1 (95% confidence interval of 11.63 to 27.30 mg mL -1 ). It was also observed that the LC 50 values calculated were more prominent at 48 h, which confirms the sensitivity of nauplii observed in previous works [3,8], suggesting that toxicity is much higher after 48 h exposure than after 24 h. Moreover, previous work showed that the crude extracts of marine Synechocystis strains reduced the survival of A. salina nauplii similarly to the results obtained here [11]. The most toxic extracts in this work were those of the filamentous forms Leptolyngbya and Microcoleus.…”
Section: Resultssupporting
confidence: 90%
“…This bioassay provides a viable tool since A. salina is a representative species of the zooplankton community. Moreover, the brine shrimp bioassay is an inexpensive test and without ethical constraints [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…This is in accordance with several studies that found that artemia greatest sensitivity to test compounds is reached at or after 48 h incubation ( Sánches-Fortún et al, 1996;Caldwell et al, 2003).…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have evaluated the toxicity of OP [20][21][22][23] as well as the protective effects of atropine and oximes in Artemia salina as a convenient alternative to toxicity screening. 22,24 Moreover, this biological model has been chosen as the testing organism considering its availability, short life cycle, high adaptability to varied nutrient resources, low cost and low variability in the population. In fact, estimation of the medium lethal dose in A salina uses a bioassay for preliminary assessment in toxicology and pharmaceutical studies by following the 3Rs policy (reduction, refinement and replacement).…”
Section: Introductionmentioning
confidence: 99%